Vibrio Bacterial Concentration in Vaname Shrimp Pond Super Intensive Technology in Takalar District, Indonesia - Jaya Asaad, A. Indra; Nessa, Natsir; Trijuno, Dody Dharmawan; Anshary, Hilal (International Journal of Environment, Agriculture and Biotechnology, 2019)
Research on the concentration of vibrio bacteria in super-intensive shrimp farms has been carried out in August to December 2018 at shrimp pond located in Takalar District, South Sulawesi, Indonesia.This study aims to determine the concentration of vibrio bacteria found in internal shrimp pond system and the dynamics that occur. The results of the study showed that the concentration of vibrio bacteria improved during the day of culture period in the ponds and outlet of the pond. However, the presence of water treatment installation at the location can reduce the concentration, so the concentration of vibrio bacteria is not a problem if released into coastal waters after being processed in water treatment.